Histopathological features of glandular atrophy of the lamina propria of the gastric mucosa during its occurrence and development - Yang-kun Wang; Dong-mei Ran; Ying-ying Li; Chao-ya Zhu; Ren-bing Zhang; Bo Jiang; Su-nan Wang (BMC Gastroenterology, 2023)
Abstract Objective To explore the histopathological features of glandular atrophy of the lamina propria of gastric mucosa during its occurrence and development. Method We performed detailed histological observation and immunohistochemical examination on the endoscopic biopsy and ESD endoscopic resection specimens of 896 patients with glandular atrophy of the lamina propria of gastric mucosa. The EnVision two-step method was used for immunohistochemical staining, and the slices were incubated with primary antibody CK7, CK20, villin, CDX2, MUC5AC, MUC6, p53 and ki-67. Hematoxylin staining was performed and observed under the microscope and statistically analyzed. Results In the initial stage of glandular atrophy of the lamina propria, the proliferation area of the deep gastric pits, and the isthmus and neck of the gastric glands are characterized by roughly normal structure of the glandular structure, increased mesenchyme, and widened space between glands. Subsequently, the gland becomes smaller in volume and less in number, especially at the base, in the gastric glandular part of the gastric unit. The disease at this stage has higher incidence, and occurs more often in the elderly who account for 64.0% (573/896) of our study group. The disease in this stage may exhibit some lesions that are physiologic (age-related degeneration) while others are pathological. Therefore, this condition is called simple glandular atrophy of the lamina propria of the gastric mucosa. When the gastric mucosal epithelium is subjected to infection or repeated infections, chemical stimuli, immune factors, and genetic factors, it can lead to the proliferation and transformation of stem cells in the proliferation area of the deep gastric pits, and the isthmus and neck of the gastric glands, forming single ducts, multiple ducts, or a proliferation of patchy cells. Then, atypical hyperplasia (intraepithelial neoplasia) presents, finally leading to gastric adenocarcinoma. Conclusion Understanding the histopathological characteristics of glandular atrophy of the lamina propria of gastric mucosa is of great significance in controlling the occurrence and development of gastric cancer.